EFEKTIVITAS METODE TOKEN KIMIA TERHADAP HASIL DAN RETENSI BELAJAR SISWA PADA MATERI SISTEM PERIODIK UNSUR DI KELAS X MAN 3 PONTIANAK - Mai Sarah; Raudhatul Fadhilah; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2019)
Student learning results and retention is still low on periodic system learning elements caused by a lack of motivation students in the periodic table system memorize elements and lack of reward when students are already able to memorize the table Periodic system of such elements. So it requires a learning method that can motivate students in deleting periodic table system elements. The study aims to determine the difference in outcomes and retention of learning between students taught with and without using the chemical token method on the periodic element system material, knowing the great effectiveness of the chemical token method of the results and Student learning retention on periodic element system materials in class X MAN 3 Pontianak. This research uses the type of experimental Quasi research with the design of control group design. The sampling technique uses saturated sampling with the X-class of MIA as the experimental class and X-grade IIS 2 as the control class. Data collection techniques using measurement, observation and interview techniques, while the data collection tools are test results and learning retention, interpreters and observation sheets. Analysis Data Using Test-T shows that there are differences in learning outcomes while learning retention differences are known through the Mann-Whitney U test with the result that there is a difference in learning retention between students taught with and without Using a chemical token method. Learning with the chemical token method affects student learning outcomes by 22.91% by medium category, and 10-day student study retention of 36.86% with high category.